Cell cycle transcription control: DREAM/MuvB and RB-E2F complexes. (2nd November 2017) - Fischer, Martin; Müller, Gerd A.
Abstract: The precise timing of cell cycle gene expression is critical for the control of cell proliferation; de-regulation of this timing promotes the formation of cancer and leads to defects during differentiation and development. Entry into and progression through S phase requires expression of genes coding for proteins that function in DNA replication. Expression of a distinct set of genes is essential to pass through mitosis and cytokinesis. Expression of these groups of cell cycle-dependent genes is regulated by the RB pocket protein family, the E2F transcription factor family, and MuvB complexes together with B-MYB and FOXM1. Distinct combinations of these transcription factors promote the transcription of the two major groups of cell cycle genes that are maximally expressed either in S phase (G1/S) or in mitosis (G2/M). In this review, we discuss recent work that has started to uncover the molecular mechanisms controlling the precisely timed expression of these genes at specific cell cycle phases, as well as the repression of the genes when a cell exits the cell cycle.